Faktor-Faktor Predisposisi Terjadinya Kehamilan Ektopik Terganggu (KET) Di Ruang Kebidanan RSUD Bangkinang Tahun 2019 - Iznirrahma Hayati (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
The main cause of the bleeding trimester is KET, abortion and molar pregnancy. KET occurs when products of conception implant, grow and develop beyond the normal endometrium. Genesis KET is the largest gynecological cases which is third in hospitals Bangkinang years 2019. There are some predisposing factor KET them are maternal age, maternal parity, KET Previous history and history of hormonal contraceptive use. The research objective was to determine the factors predisposing KET in space Bangkinang Obstetrics Hospital in 2019. Methode performed using analytical research with case control study design with a population of 314 mothers then retrieved a sample of 62 mothers who consisted of 31 mothers in the sample cases were taken using purposive sampling and 31 mothers as a control sample taken using systematic random sampling technique. The analysis used were univariate and bivariate using Chi Square test, it was found that four independent variables (age, parity, previous KET history and history of hormonal contraception has a significant relationship to the occurrence of KET for the value pvalue < a (0.05) . Hoped that staff health can provide antenatal care according to the standard so that if there is a sign of danger to the mother can be immediately detected.